2023
DOI: 10.1021/acs.jmedchem.2c01964
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent and Orally Bioavailable Zwitterionic Series of Selective Estrogen Receptor Degrader-Antagonists

Abstract: Herein, we report the optimization of a metasubstituted series of selective estrogen receptor degrader (SERD) antagonists for the treatment of ER+ breast cancer. Structure-based design together with the use of modeling and NMR to favor the bioactive conformation led to a highly potent series of basic SERDs with promising physicochemical properties. Issues with hERG activity resulted in a strategy of zwitterion formation and ultimately in the identification of 38. This compound was shown to be a highly potent S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Recently, Scott et al reported a series of zwitterion-containing SERD antagonists for the treatment of ER+ BC . Among them, compound 18 was shown to be a highly potent SERD capable of effectively degrading ERα in both MCF-7 and CAMA-1 cell lines (Figure ).…”
Section: Zwitterionic Series Of Serdsmentioning
confidence: 88%
See 3 more Smart Citations
“…Recently, Scott et al reported a series of zwitterion-containing SERD antagonists for the treatment of ER+ BC . Among them, compound 18 was shown to be a highly potent SERD capable of effectively degrading ERα in both MCF-7 and CAMA-1 cell lines (Figure ).…”
Section: Zwitterionic Series Of Serdsmentioning
confidence: 88%
“…Due to the presence of an acid moiety, compound 18 also has a very low PPB, which resulted in a high fraction unbound in PPB assays across species (>10% free). The CYP450 profile of this compound showed no significant inhibition, with IC 50 > 30 μM in all five isoforms (CYP1A2, CYP2C19, CYP2C9, CYP2D6, and CYP3A4) …”
Section: Zwitterionic Series Of Serdsmentioning
confidence: 94%
See 2 more Smart Citations
“…UPLC−MS: 1.49 min, purity >95%; MS (ESI) m/z: calcd, 792.41 for C 49 H 53 N 5 O 5 [M + H] + ; found, 792.5; 1 H NMR (400 MHz, MeOD): δ 7.93 (s, 2H), 7.20 (d, J = 8.8 Hz, 2H), 7.17−7.09 (m, 3H), 6.84 (dd, J = 7.5, 1.7 Hz, 2H), 6.72− 6.60 (m, 4H), 6.53 (dd, J = 8.3, 2.6 Hz, 1H), 5.17 (dd, J = 12.6, 5.4 Hz, 1H), 4.94 (s, 4H), 4.37 (d, J = 5.3 Hz, 1H), 3.82−3.58 (m, 4H), 3.56− 3.41 (m, 5H), 3.24−2.97 (m, 6H), 2.94−2.66 (m, 3H), 2.41−2.10 (m, 8H), 1.88−1.70 (m, 5H). (21). A mixture of intermediate 48 (500 mg, 1.0 equiv), methyl azetidine-3-carboxylate hydrochloride (232 mg, 2.0 equiv), Pd(OAc) 2 (34 mg, 0.2 equiv), BINAP (143 mg, 0.3 equiv), and Cs 2 CO 3 (996 mg, 4.0 equiv) in toluene (15 mL) was degassed and purged with 3 times N 2 , and the reaction was stirred at 100 °C under a N 2 atmosphere for 16 h. After cooling to rt, the reaction mixture was diluted with DCM and filtered through Celite to remove insoluble catalyst and salts, and the filter cake was washed with DCM.…”
Section: -(26-dioxopiperidin-3-yl)-6-(5-(1-(4-((1r2smentioning
confidence: 99%